Intracranial aneurysms treated with a novel coated low-profile flow diverter (p48 HPC): a single-center experience and an illustrative case series - Krug, Nadja; Kirschke, Jan S.; Maegerlein, Christian; Kreiser, Kornelia; Wostrack, Maria; Meyer, Bernhard; Albrecht, Carolin; Zimmer, Claus; Boeckh-Behrens, Tobias; Sepp, Dominik (Brain Sciences, 2025)
Background/Objectives: The p48 MW HPC is a novel low-profile flow diverter covered by a hydrophilic polymer coating with antithrombogenic properties, which may reduce ischemic complications and enable a single antiplatelet therapy after insertion of the stent. In this single-center experience, we describe the efficacy of this device, focusing on the illustration of different therapeutic indications and the outcome in various clinical settings with regard to vessel anatomy, bleeding state, and aneurysm configuration. Methods: We retrospectively reviewed our database for all patients being treated with a p48 MW HPC flow diverter between February 2019 and July 2021. The efficacy of the treatment was evaluated according to the O’Kelly-Marotta (OKM) scale in the last digital subtraction angiography (DSA) follow-up. Information on complications and medications were collected from our medical records. In addition, to illustrate different indications and clinical settings, we present six of these cases in closer detail. Results: 18 aneurysms in 14 patients were treated with the p48 MW HPC flow diverter and in one case with an additional Derivo device. Periprocedural events occurred in 28.6% of the treated patients, which were all successfully resolved within the same session. Follow-up examination information was available for 67% of patients, of which 75% showed complete occlusion of the aneurysm and 83.3% showed a favorable occlusion result (OKM C-D). Two patients with ruptured aneurysms received a single antiplatelet therapy with ASA without thrombotic complications, at least in the short term. New braid deformation patterns were observed in 16.6% at the follow-up examination, but none with subsequent clinical significance. Conclusions: The p48 MW HPC is safe and effective in the treatment of a wide spectrum of differently configurated, ruptured, and unruptured aneurysms. Single antiplatelet therapy might be an option in selected cases.
Gesehen am 28.08.2025